Altered expression of caspases‐4 and ‐5 during inflammatory bowel disease and colorectal cancer: Diagnostic and therapeutic potential. (6th May 2015) - Flood, B.; Oficjalska, K.; Laukens, D.; Fay, J.; O'Grady, A.; Caiazza, F.; Heetun, Z.; Mills, K. H. G.; Sheahan, K.; Ryan, E. J.; Doherty, G. A.; Kay, E.; et al.
Summary: Caspases are a group of proteolytic enzymes involved in the co‐ordination of cellular processes, including cellular homeostasis, inflammation and apoptosis. Altered activity of caspases, particularly caspase‐1, has been implicated in the development of intestinal diseases, such as inflammatory bowel disease (IBD) and colorectal cancer (CRC). However, the involvement of two related inflammatory caspase members, caspases‐4 and ‐5, during intestinal homeostasis and disease has not yet been established. This study demonstrates that caspases‐4 and ‐5 are involved in IBD‐associated intestinal inflammation. Furthermore, we found a clear correlation between stromal caspase‐4 and ‐5 expression levels, inflammation and disease activity in ulcerative colitis patients. Deregulated intestinal inflammation in IBD patients is associated with an increased risk of developing CRC. We found robust expression of caspases‐4 and ‐5 within intestinal epithelial cells, exclusively within neoplastic tissue, of colorectal tumours. An examination of adjacent normal, inflamed and tumour tissue from patients with colitis‐associated CRC confirmed that stromal expression of caspases‐4 and ‐5 is increased in inflamed and dysplastic tissue, while epithelial expression is restricted to neoplastic tissue. In addition to identifying caspases‐4 and ‐5 as potential targets for limiting intestinal inflammation, this study has identified epithelial‐expressed caspases‐4 and ‐5 as biomarkers with diagnostic and therapeutic potential in CRC.